When Targets Blame Their Organization for Sexual Harassment: A Multilevel Investigation of Within-Person Appraisals. (February 2018) - Madera, Juan M.
Very little is known about the targets' appraisal process related to when targets blame the organization for sexual harassment. Thus, the purpose of the current study was to examine targets' appraisal process of blaming the organization for sexual harassment incidents across multiple experiences of sexual harassment. Specifically, the current study used an experience sampling method (ESM) that captures a within-person approach to determine how the intensity of sexual harassment incidents affects the appraisal of fear of retaliation and perceived distress, which then influence organizational blame for sexual harassment across multiple experiences of sexual harassment. The study used a sample of 76 college students working in frontline service jobs who completed ratings of the variables three times, one month apart for a total of 228 ESM observations nested within participants. Random coefficient modeling was used to analyze multilevel models. The results showed that the intensity of sexual harassment incidents does lead to organizational blame. The results also showed that fear of retaliation and perceived distress mediated the relationship between the intensity of sexual harassment incidents and organizational blame. The most important implication for theory is the current article's focus on the within-person appraisals over multiple incidents, showing that across multiple incidents of sexual harassment, the same employee has varying degrees of fear of retaliation, perceived distress, and organizational blame. Thus, the results of the current study underscore that each sexual harassment incident and employee appraisal differs on an event-by-event basis.